1993
DOI: 10.1111/j.1398-9995.1993.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to the insect allergen Chi t I in aquarists and fish‐food factory workers

Abstract: Our examination of 225 subjects who had been exposed to the insect allergen Chi t I involved the degree of allergen exposure, the exposure-associated symptoms, and their relationship to the presence of specific IgE and IgG antibodies as well as sensitization to ubiquitous allergens. It could be shown that specific IgE antibodies found in 34% of these subjects were closely associated with symptoms (P < 0.01), whereas no relationship between IgG antibodies and complaints could be observed. Conjunctivitis (63%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…It has been reported that Cladotanytarsus lewisi occurred in enormous numbers in the Nile basins in Sudan and caused severe respiratory diseases in people living close to the Nile (10). Chironomid larvae were widely used as fish food in Germany and elicit occupational allergic diseases in a significant number of people who were exposed to these larvae (1,15).…”
mentioning
confidence: 99%
“…It has been reported that Cladotanytarsus lewisi occurred in enormous numbers in the Nile basins in Sudan and caused severe respiratory diseases in people living close to the Nile (10). Chironomid larvae were widely used as fish food in Germany and elicit occupational allergic diseases in a significant number of people who were exposed to these larvae (1,15).…”
mentioning
confidence: 99%
“…A number of Diptera species have been reported to be allergenic, including fruit flies (Drosophilidae), screwworm flies, Cochliomyia hominivorax (Coquerel), other blow flies (Caliphoridae), and midges (Chironomidae). 2,7,8,12,22 Spieksma et al 15 reported the presence of respiratory symptoms in one third of laboratory workers exposed to the fruit fly, Drosophila melanogaster (Meigen). Baur and Liebers 2 reported increased risks of sensitization and of bronchial asthma in subjects exposed to midges.…”
Section: Discussionmentioning
confidence: 98%
“…Da die Larven als Trockenfutter in der Fischzucht in Deutschland häufig verwendet werden, sind Fischfutterfabrikarbeiter, Zoohändler und (Hobby-)Aquarianer ihnen gegenüber exponiert und kön-nen daher von Sensibilisierungen betroffen sein. Die Hämoglobine insbesondere der Art Chironomus thummi sind strukturell, immunologisch und klinisch sehr genau untersuchte potente Allergene [56,57]. Studien belegen, dass durchschnittlich 20% der exponierten Personen sensibilisiert sind [57].…”
Section: Allergenquellen Tierischen Ursprungsunclassified
“…Die Hämoglobine insbesondere der Art Chironomus thummi sind strukturell, immunologisch und klinisch sehr genau untersuchte potente Allergene [56,57]. Studien belegen, dass durchschnittlich 20% der exponierten Personen sensibilisiert sind [57].…”
Section: Allergenquellen Tierischen Ursprungsunclassified